Bill Marxmiller with Prize-Winning Steer, 1949 (1949)
Cal Poly sophomore Bill Marxmiller's 1,000-pound shorthorn steer "Poly Jock" won the top award as Grand Champion at the Great Western Livestock Show in Los Angeles, 1949. Animal husbandry instructor Harry Parker (left) congratulates the proud winners.